Genetic relationships within social groups influence the application of the Judas technique: A case study with wild dromedary camels - Spencer, P.; Hampton, J.; Pacioni, Carlo; Kennedy, M.; Saalfeld, K.; Rose, K.; Woolnough, A. (2015)
© 2014 The Wildlife Society. The Judas animal control technique relies on the social nature of some invasive species to betray the location of their companions. It is an effective method of enhancing shooting programs in highly gregarious mammal species. We used social genetic data to examine the utility of the Judas technique in a novel species: wild dromedary camels (Camelus dromedarius). Firstly, we used molecular data (13 microsatellite markers from 1,050 camels) to characterize genetic diversity and relatedness within and between observed social groups. Genetic estimates of relatedness between pairs within a group (r = -0.058) were not different from a comparison between any 2 randomly selected individuals. We did not find relatedness within and between social groups to be significantly different for 78% of social groups, suggesting a fission-fusion social structure conducive to applying the Judas technique. Secondly, we performed an operational trial of the Judas technique to assess the predictions of the genetic data. We tracked 10 collared Judas camels using a combination of satellite- and radio-telemetry for 9.0 ± 5.0 (mean ± SD) months between 2008 and 2010. We found Judas animals with a cohort of animals on 96% of occasions. Cohorts displayed no significant size difference prior to shooting (9.3 ± 9.9 animals), and after shooting (9.2 ± 7.5 animals). Genetic and operational data indicate that the Judas technique may be of utility in controlling camels at low population densities. This study also suggests that social genetic data can be used to assess applicability of the Judas technique for novel species.